Multiple Site-Specific One-Pot Synthesis of Two Proteins by the Bio-Orthogonal Flexizyme System - Xiao, Qiuyun; Liu, Zihan; Zhao, Xuan; Xiong, Hai (Frontiers in Bioengineering and Biotechnology, 2020)
Lysine acetylation is a reversible post-translational modification (PTM) vastly employed in many biological events, including regulating gene expression and dynamic transitions in chromatin remodeling. We have developed the first one-pot bio-orthogonal flexizyme system in which both acetyl-lysine (AcK) and non-hydrolysable thioacetyl-lysine (ThioAcK) were site-specifically incorporated into human histone H3 and H4 at different lysine positions in vitro, either individually or in pairs. In addition, the high accuracy of this system moving toward one-pot synthesis of desired histone variants is also reported.